THE EFFECT OF SHARIA ACCOUNTING KNOWLEDGE, RELIGIUSITY, STUDENT'S PERCEPTION, MOTIVATION ON STUDENT'S INTEREST IN CAREER IN SHARIA FINANCIAL INSTITUTIONS (Empirical Studies in West Java Accounting Study Program Students) - Asep Kurniawan; Fauzan As Shidik; Sri Mulyati (STIESA Press, 2022)
The rapid development of the business world provides diverse job opportunities for the workforce, especially progress in the sharia business world in Indonesia, of course, it will continue to be accompanied by adequate infrastructure, including experts in the field of sharia business it self. The purpose of this study was to determine the relationship between knowledge of sharia accounting, religiosity, student perceptions and motivation to the interest of accounting students to have a career in sharia institutions. The context in this study is accounting students at universities in West Java. This study uses quantitative research methods using questionnaires. The sample selection used by the researcher is a random sampling technique This study aims to examine whether there is a relationship between Islamic accounting knowledge, religiosity, student perceptions, and motivation, on student interest in a career in Islamic financial institutions. This research was conducted by examining a sample of 210 students who were in West Java in 2022. The research method used in this study was survey research directly to the field and via whatsapp